2005
DOI: 10.1128/jvi.79.4.2066-2078.2005
|View full text |Cite
|
Sign up to set email alerts
|

Leucine-Specific, Functional Interactions between Human Immunodeficiency Virus Type 1 Nef and Adaptor Protein Complexes

Abstract: The human immunodeficiency virus type 1 virulence protein Nef interacts with the endosomal sorting machinery via a leucine-based motif. Similar sequences within the cytoplasmic domains of cellular transmembrane proteins bind to the adaptor protein (AP) complexes of coated vesicles to modulate protein traffic, but the molecular basis of the interactions between these motifs and the heterotetrameric complexes is controversial. To identify the target of the Nef leucine motif, the native sequence was replaced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
43
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 52 publications
(88 reference statements)
7
43
0
1
Order By: Relevance
“…In addition to AP-2, formed by α, β2, μ2 and σ2 subunits (Table S1), two other AP complexes, AP-1 (γ1, β1, μ1 and σ1) and AP-3 (δ, β3, μ3 and σ3), are binding partners of Nef (Bresnahan et al, 1998;Chaudhuri et al, 2007;Coleman et al, 2005;Doray et al, 2007;Greenberg et al, 1998;Janvier et al, 2003a,b;Mattera et al, 2011). However, the role of the Nef interaction with AP-1 or AP-3 in CD4 downregulation is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to AP-2, formed by α, β2, μ2 and σ2 subunits (Table S1), two other AP complexes, AP-1 (γ1, β1, μ1 and σ1) and AP-3 (δ, β3, μ3 and σ3), are binding partners of Nef (Bresnahan et al, 1998;Chaudhuri et al, 2007;Coleman et al, 2005;Doray et al, 2007;Greenberg et al, 1998;Janvier et al, 2003a,b;Mattera et al, 2011). However, the role of the Nef interaction with AP-1 or AP-3 in CD4 downregulation is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…These isoforms include two γ (γ1 and γ2), two μ1 (μ1A and μ1B) and three σ1 (σ1A, σ1B and σ1C) subunits for AP-1; two α subunits for AP-2; and two μ3 (μ3A and μ3B), two β3 (β3A and β3B) and two σ3 (σ3A and σ3B) subunits for AP-3 (Boehm and Bonifacino, 2002). Nef binds to APs through a conserved 'dileucine-based' (D/E)xxxL(L/I) consensus motif in the viral protein (Craig et al, 1998;Greenberg et al, 1998), which is recognized by hemi-complexes comprising the γ1-σ1, α-σ2 and δ-σ3 subunits of the respective AP (Chaudhuri et al, 2007;Coleman et al, 2005;Doray et al, 2007;Janvier et al, 2003a,b). Subsequently, it has been shown that γ2 is also capable of mediating a σ1-dependent interaction with Nef (Mattera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the type of internalization motif (i.e. tyrosine-or di-leucine-based) present on a particular protein can have functional consequences for trafficking (38). Our effort to elucidate the mechanism by which Kir2.3 is controlled by endocytosis expands the repertoire of signals known to interact with AP complexes.…”
mentioning
confidence: 99%
“…In addition to AP-2, formed by α, β2, μ2 and σ2 subunits (Table S1), two other AP complexes, AP-1 (γ1, β1, μ1 and σ1) and AP-3 (δ, β3, μ3 and σ3), are binding partners of Nef (Bresnahan et al, 1998;Chaudhuri et al, 2007;Coleman et al, 2005;Doray et al, 2007;Greenberg et al, 1998; Janvier et al, 2003a,b;. However, the role of the Nef interaction with AP-1 or AP-3 in CD4 downregulation is poorly understood.…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…These isoforms include two γ (γ1 and γ2), two μ1 (μ1A and μ1B) and three σ1 (σ1A, σ1B and σ1C) subunits for AP-1; two α subunits for AP-2; and two μ3 (μ3A and μ3B), two β3 (β3A and β3B) and two σ3 (σ3A and σ3B) subunits for AP-3 (Boehm and Bonifacino, 2002). Nef binds to APs through a conserved 'dileucine-based' (D/E)xxxL(L/I) consensus motif in the viral protein (Craig et al, 1998;Greenberg et al, 1998), which is recognized by hemi-complexes comprising the γ1-σ1, α-σ2 and δ-σ3 subunits of the respective AP (Chaudhuri et al, 2007;Coleman et al, 2005;Doray et al, 2007; Janvier et al, 2003a,b). Subsequently, it has been shown that γ2 is also capable of mediating a σ1-dependent interaction with Nef .…”
mentioning
confidence: 99%